A protocol for identifying archaeological parenchyma using microCT: Steps towards a virtual reference collection. (December 2022) - Barron, Aleese; Denham, Tim
Highlights: MicroCT scanning of key archaeological parenchyma species to form first virtual 3D reference collection. Development of microCT scanning and visualisation protocol for the imaging and identification of archaeological parenchyma. 3D nature of microCT scanning increases the potential for taxonomic identification of archaeological parenchyma fragments. Abstract: The investigation of archaeological parenchyma derived from underground storage organs (USOs) is under-represented in archaeobotany globally. Although some regional reference collections have been assembled and applied to archaeobotanical materials, these are not generally accessible to researchers. Here, the initial steps in the development of a virtual database for archaeological parenchyma are detailed. Foremost, a protocol for the microCT scanning and virtual reconstruction of modern reference material and also of archaeological parenchyma is detailed. The protocol enables a 3D virtual representation of scanned materials to be reconstructed at high resolution (the highest resolution typically being between 2 and 3 µm), which can be interrogated qualitatively (user-defined) and quantitatively (using automated segmentation, algorithms and eventually deep learning neural networks) to enable taxonomic differentiation and comparability. The protocol is presented to enable replicability of analysis and also to ensure standardization in the future development of an online, open access and editable, 3D virtual database of modern reference samples and archaeological parenchyma.